Reference sites of threatened riverine Atlantic forest in upper Rio Doce watershed - Figueiredo, João C. G.; Negreiros, Daniel; Ramos, Letícia; Paiva, Dario C.; Oki, Yumi; Justino, Wénita S.; Santos, Rubens M.; Aguilar, Ramiro; Nunes, Yule R.F.; Fernandes, G. Wilson (Nature Conservation Research: Заповедная наука, 2024)
The most important condition of ecological restoration is the identification of reference ecosystems, which function as a guide for assertive practice with which biological integrity and ecosystem structure and function can be compared. For restoration and conservation projects to be effective in the current scenario of biodiversity and ecosystem services decay worldwide, it is fundamental to understand the soil-plant interactions in each environment. In this study, we evaluated the structure and composition of the flora in 45 plots, equally distributed in three preserved areas (reference ecosystems) of Atlantic Forest in the upper Rio Doce watershed, Southeast Brazil. We also tested whether differences in species composition were influenced by edaphic factors, both in the adult tree and sapling strata. In both tree and sapling strata, Fabaceae was the species-richest family, followed by Myrtaceae, and Lauraceae. The Fabaceae family also showed the highest importance value for both strata. The soils of the riparian forests were highly heterogeneous among the studied sites. Co-inertia analyses indicated a clear edaphic-floristic gradient in both tree (RV = 0.467; p < 0.001) and sapling (RV = 0.478; p < 0.001) strata, with a connection of 46.7% and 47.8% between the edaphic and floristic matrices for trees and saplings, respectively. We identified the groups of tree and sapling strata species that were strongly associated with either nutritionally richer or poorer soils on each studied site. Understanding how ecological and life-history traits of plant species relate with edaphic factors is an important step to provide scientific-based knowledge to support policies for ecosystem recovery and restoration in the stretches of the Rio Doce watershed.